Metode Bernyanyi dalam Pembelajaran Mufradat di Madrasah Tsanawiyah Nurul Hikmah Haurgeulis - Anisa Fitriani; Iis Susiawati; Dewi Utami (Journal on Education, 2023)
Variations in teacher methods and flexibility in the learning process will be able to create more effective learning, because it can reduce boredom during learning, one of which is the singing method. This study aims to find out and understand the application of the singing method in the mufradat learning of madrasah students in Haurgeulis, Indramayu. Qualitative research with this descriptive method describes a state of the object under study. The population is teachers and students of class VII, with a sample of Arabic language teachers and students of class VII B. The data will be collected using observation, interview and documentation techniques. The results of this study are that the application of the singing method in learning Arabic mufradat in class VII MTs Nurul Hikmah Haurgeulis Indramayu can be said to be good, because the educators carry out three stages of learning, namely main activities, core activities and closing activities. The application of this singing method also has advantages and disadvantages, the advantage is that it can cause a feeling of joy and delight in students and increases a sense of enthusiasm, students more easily understand and memorize the material presented. While the drawback is that this method is not suitable for upper class students because the material presented is different and broader and not suitable for quiet students.